Animal II. (Wien : Fotogalerie Wien, 2001)
Aigner, Rolf ; Andraschek, Iris ; Bagazgoitia, Felix G. ; Baumgartner, Elfriede ; Bertram, Eva ; Böhmer, Ursula ; Brunner-Szabo, Eva ; Burger, Joerg ; Cibulka, Heinz ; Dera, Cor ; Dworak, Andreas ; Elsinger, Christine ; Fabsits, Rita ; Fankhauser, Ingrid ; Ferrari, Giuliano ; Forster, Jim ; Franke, Verena ; Freiler, Thomas ; Frey, Magdalena ; Halwax, Erika ; Hoedt, Ralf ; Hudson, Carol ; Iglar, Rainer ; Kandl, Leo ; Kiraly, Josif ; Kocan, Robo ; Koller, Alexander ; Kuss, Kai ; Zück, Christina ; Lang, Markus ; Lázár, Erich ; Leitner, Paul Albert ; Lobnig, Hubert ; Mejchar, Elfriede ; Michlmayr, Michael ; Minyó Szert Károly ; Mirtl, Walter ; Moser-Wagner, Gertrude ; Mühlbacher, Isabelle ; Neubauer, Ruth ; Neudeck, Lydia ; Otte, Hans ; Palme, Waltraud ; Pardatscher, Martin ; Phelps, Andrew ; PIWI ; Radochonska, Lucia ; Schneider, Manfred ; Seidl, Herman ; Simak, Fritz ; Spiluttini, Margherita ; Straeten, Andrea Van Der ; Tambour, Evelin ; Vanscó, Zoltán ; Verdi, Margherita ; Wetzelsdorfer, Alfred ; Willmann, Manfred ; Zahornicky, Robert
biog. per kunstenaar
Animal II, Fotogalerie Wien, 7. Juni - 30. Juni 2001
Duits
kunstcatalogus